PENEGAKKAN ASAS EQUALITY BEFORE THE LAW DI MASA PANDEMI TERHADAP PEMBATASAN AKTIVITAS SOSIAL - Fadli, Fandi; Faharudin, Faharudin; Nasrin, Nasrin (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
The entire world community agrees that the right to health is a fundamental right that every human being has. The right to health, which was previously seen as just a personal matter related to fate or God's grace, has now experienced a huge paradigm shift to become a legal right which is of course guaranteed by the state. In the midst of the Covid-19 pandemic which has spread almost throughout In the Indonesian region, the Government must be alert in issuing various strategic policies so that it can carry out its obligations to always guarantee the fulfillment of the right to health for all people, of course by enforcing laws based on the principle of equality before the law. This research found that the Government was too slow in taking anticipatory and mitigation measures in tackling the corona pandemic. In the end, the Government declared a Public Health Emergency status and chose Restrictions on social activities as an option to respond to the Public Health Emergency, besides that the Government also had to pay attention to the economic and fiscal sectors according to the country's conditions and capabilities.